An Analysis of Students' Reading Ability in Identifying Generic Structure of News Item Text - Widya Juli Astria (Fakultas Sastra Universitas Ekasakti, 2019)
This research aims to determine the ability of students to identify the generic structure of the news item text. This research uses a descriptive method. Data is taken through examinations in the form of multiple choice questions. The results showed that the ability of students to identify newsworthy events, event backgrounds and sources of news item texts was at a moderate level. This is evidenced by the percentage of student scores for each of the generic structures is 58.46%, 69, 23% and 61, 54%. Therefore, teachers are advised to discuss more and provide training on generic structure of the news item text. Then, students are advised to study harder to understand and do generic structure exercises from news item text. Furthermore, the next researcher is expected to conduct research related to the problems faced by students in identifying the generic structure of the news item text.